Dynamics of Revitalization Program Towards Fair and Beneficial Renewal of Oil Palm Plantation in Indonesia - Firman Saputra; Abdullah Sulaiman (PT. ALHAFI BERKAH INDONESIA, 2025)
The oil palm plantation revitalization program in Indonesia is a response to the various structural, social, and environmental challenges faced by this sector. The dynamics of the program's implementation reflect the efforts of the government and stakeholders in creating a plantation system that is more equitable, sustainable, and beneficial to the community, especially smallholders. Through the policy of replanting smallholder oil palm (PSR), improving governance, and providing technical and financial support, revitalization is expected to increase productivity, improve the distribution of economic benefits, and reduce ecological impacts. However, various obstacles, such as overlapping regulations, gaps in access, and weak supervision are still real challenges in this renewal process. This paper explores these dynamics by highlighting the roles of key actors, implementation mechanisms, and potential solutions to achieve revitalization goals inclusively and equitably.